System and integrity of educational work in the establishment of higher education - Денисова, Н. В. (Scientific notes of the pedagogical department, 2018)
The urgency of the problem of the integrity of the educational work system in the establishments of higher education is disclosed in the article. It is organically connected with the studies, aimed at the general goal - the formation of all-round developed personality. The contents, forms, methods of such work are highlighted. Its groundbreaking basis is the coordination of the activities of all subdivisions of the branch, a practical psychologist, students’ self-government and a student scientific society. An important direction in the integral process of education is the educational work at the hostel. It has a common goal and meaningful content. In a hostel, students acquire the first serious self-existence: they cook, wash and demonstrate self-service skills. Students who live in the hostel together with the educator organize leisure activities, initiate cognitive activities. The significance of practical training in the system of educational work is determined. Its components are the formation of professional orientation and motives of professional activity on the basis of the transition of social and professional requirements into the system of value orientations and activity of the personality; the formation of the professional duty, which is the set of requirements and moral principles that nowadays society requires from the person; professional honor and dignity; professional conscience, etc. The role of teaching and methodical work is considered.  It provides the conditions for the harmonious development of the person, his/her creative potential, readiness to make competent decisions, sharing opinions, promoting independent thinking of students, their interest in solving the problems in education. The attention is focused on the aesthetic design of the interior and adjoining territory of the institution. It also has a positive effect on the education of the individual. Effective educational technologies are listed, in particular, ICT and interactive. The aspects of the educational work directed on the interaction of the intellectual, emotional-volitional, psychomotor spheres of the individual are determined. Attention is paid to the style of pedagogical activity in in contemporary educational environment. The directions of work of the tutor are characterized.